ENTITAS GEREJA DALAM BERPOLITIK DI INDONESIA (TINJAUAN SUDUT ETIKA KRISTEN) - Ni Nyoman Fransiska M.Th (Sekolah Tinggi Teologia Wesley Methodist Indonesia, 2019)
This paper discusses the political attitudes of Christians towards politics in Indonesia. Christians have been actively involved in the resistance movement against the Dutch colonialists, participated in establishing the country, formulated ideology and ratified the 1945 Constitution, participated in maintaining Indonesia's independence through the war of independence and played an active role in building the Indonesian nation. The state was created by God to carry out its function of creating justice, protecting and serving society. Therefore Christians are also called to participate in the creation of Peace (Welfare) in the country, because in a prosperous and peaceful country, the church can live better (Jer.29: 7).